The effect of physical and psychosocial safety climate on the health of Malaysian healthcare workers / Loh May Young - Loh, May Young (2017)
Research showed that healthcare workers are prone to be involved in workplace illnesses, injuries and accidents. Unfortunately, while safety climate has been documented as one of the most influential factors in preventing workplace injuries and illnesses, little study has been done in Malaysia. This study aims to understand the impact of both physical and psychosocial safety climate on the general health among Malaysian frontline healthcare workers, via the Job Demands and Resources model. So far, there is no study has examined both physical and psychosocial safety climate, as the antecedents of organizational job designs and workers’ physical and psychological health, simultaneously to date. Current study innovates by integrating both physical and psychosocial aspect of safety climate, testing their relationship with the job designs and workers’ individual outcome variables, including emotional exhaustion and general health. This study purported to explore how these two facet-specific organizational climates might work together in influencing a healthcare organization’s work conditions. This study can be best described as a cross-sectional quantitative multilevel study. The sample consists of 951 healthcare workers nested in 74 workgroups from a Malaysian hospital. A self-reported questionnaire was used in this study. The present findings confirmed that psychosocial safety climate is better than physical safety climate in predicting some working conditions (i.e. emotional demands [γ = -.28, SE = .12, p< .05; γ = -.05, SE = .15, not significant (ns)] and rewards [γ = .25, SE = .12, p < .05; γ = .27, SE = .14, ns], but not cognitive demands) and individual health outcomes (i.e. emotional exhaustion and general health complaints). Current study has also tested the between-group effect of working conditions on individual health outcomes, finding that only group-level of emotional demands but not rewards were related to emotional exhaustion (γ = .50, SE = .11, p < .001) and general health complaints (γ = .39, SE = .13, p < .005). Monte Carlo stimulation analysis was conducted to confirm that emotional demands mediated the relationship of PSC and both emotional exhaustion (95% Confidence Interval [CI], Lower Level [LL] = -.2731, Upper Level [UL] = -.0189) and general health outcomes (95% CI, LL = -.2127, UL = -.0073). As predicted, psychosocial safety climate has a greater impact on job design and individual outcomes when compared to safety climate. In other words, psychosocial safety climate is important to ensure a favourable working conditions and maintain workers’ health. Generally, the findings support that psychosocial safety climate as the target for occupational health intervention and a major emphasis for reducing workplaces hazards. As a final note, this study will be able to extend the existing knowledge on the occupational health of Malaysian healthcare setting by examining safety climate and its effect on health outcome variables among the workers. The results are expected to be useful for intervention design and policy makings by practitioners.